Multimerized epitope tags for high-sensitivity protein detection. - Stowers, R.S. (G3 : genes - genomes - genetics, 2025)
A detailed understanding of the function of a gene requires knowledge of the cellular and subcellular distribution of its encoded protein(s). For proteins expressed at low levels, antibodies that recognize single epitopes may not be sufficient for visualizing expression. To enhance the sensitivity of protein detection, tandem repeat multimers of the commonly used epitope tags V5, HA, MYC, FLAG, ALFA, and OLLAS were developed that encode up to 80X copies of each tag, an 8-fold increase over currently available options for epitope multimer tagging. As proof-of-principle, conditional alleles of vGlut containing the 40XV5 and 40XMYC epitope tag multimers were validated in vivo in Drosophila. Both epitope-tagged proteins were determined to exhibit synaptic localization in the adult brain and larval neuromuscular junction similar to that of endogenous vGlut. They were also conditionally expressed in subsets of adult brain neurons and observed to exhibit robust, easily detectable expression in presynaptic terminals even in single neurons. These highly multimerized epitope tags will facilitate any type of experiment using antibody detection of proteins that would benefit from enhanced sensitivity.